Making endoscopy mobile: a novel initiative for public healthcare - Talukdar, R.; Nageshwar Reddy, D. (Endoscopy, 2012)
Public healthcare has progressed immensely in the past few decades. However, the rural masses in the developing and underdeveloped countries very often have limited access to the advanced healthcare technology. At the Asian Institute of Gastroenterology, Hyderabad, India, the Rural Health Care Project has been initiated in an attempt to provide cost-effective gastrointestinal care to the rural population. The Project was implemented by traveling to remote rural areas in a bus that had been converted into a mobile hospital and equipped with basic diagnostic facilities including a custom-made endoscopy unit. The mobile hospital and endoscopy unit is accompanied by a telemedicine vehicle that transmits all procedures and data to the main telemedicine center at the parent institute in Hyderabad. Our efforts have resulted in cost-effective management and robust data collection of several common gastrointestinal illnesses in remote rural areas of the Indian state of Andhra Pradesh. To date, 32756 endoscopic procedures have been carried out in a population of over 10 million people spanning 4837 villages. Overall, 72 % of the population has had a positive finding on upper gastrointestinal endoscopy (primarily related to acid peptic diseases). Interestingly, < 1 % of the population have had colonic polyps on screening colonoscopy, whereas the prevalence of infective colitis has been high. This whole exercise has produced a high level of satisfaction among both beneficiaries and care-givers; it has also offered doctors in training the opportunity to encounter and manage common public health-related problems. This program is funded by philanthropic donations.